Revealing the Vital Role of MSMEs in Community Workforce Empowerment - Kautsar, Namal; Maulana, Denny; Mahfudz, Mahfudz; Raharjo, Susilo Toto (LifeSciFi, 2025)
Empowering the regional economy through the development of micro, small, and medium enterprises (MSMEs) plays a vital role in fostering inclusive and sustainable economic growth at the local level. This research investigates the success and challenges faced by MSMEs in Thamrin City, focusing on strategies to enhance their development and contribute to local economic empowerment. Employing a descriptive approach, the study analyzes employment trends within MSMEs from 2019 to 2023, complemented by interviews with MSME owners and key stakeholders. The findings reveal that while MSMEs in Thamrin City face significant challenges such as limited access to funding, restricted market reach, and resistance to innovation, these hurdles can be addressed through strategic initiatives. Strong human resource (HR) capabilities, coupled with effective marketing strategies, are identified as critical factors in enabling small businesses to overcome these barriers and achieve sustainable growth. The study contributes to a deeper understanding of the pivotal role that MSMEs play in supporting regional economic development. It highlights the necessity of targeted empowerment policies and initiatives to facilitate the expansion of small businesses, which, in turn, enhances community well-being. By focusing on capacity-building and market development, stakeholders can create an environment that fosters the resilience and competitiveness of MSMEs. This research underscores the need for collaborative efforts between governments, financial institutions, and local communities to unlock the full potential of MSMEs as drivers of economic progress and social inclusion.